In situ observation of bainitic transformation behavior in medium carbon bainitic steel - Xiaojie Zhao; Zhinan Yang; Chunlei Zheng; Fucheng Zhang; Xiaoyan Long (Journal of Materials Research and Technology, 2022)
The bainitic transformation behavior of samples with different scales was observed with dilatometer (DIL), high-temperature laser scanning confocal microscope (LCSM), and environmental transmission electron microscope (ETEM). Results show that the bainitic transformation behavior varies according to the geometrical size of samples, and it is mainly manifested in transformation units and growth rates of units. The nucleation and growth processes of finer bainitic subunits, accompanied by dislocation movement, were observed by ETEM. At the same time, the radial lengthening and broadening rates of bainitic ferrite (BF) plates were quantitatively measured. The former is 82 times the latter. The broadening time of BF plates accounts for 97.3% of the total time of the growth.